The Kasambu Tradition Moral Values Of Muna Ethnic In Southeast Sulawesi - Shandy, Cyndi Mareta (Globish: An English-Indonesian Journal for English, Education, and Culture, 2024)
Along with the development increasingly advanced human civilization, Oral traditions began to be pushed aside, some even became extinct from society. One of the traditions words whose extinction needs to be realized is a kasambu tradition that exists in the Muna tribal community. the author is very interested in discussing the traditions of the Muna tribe of Southeast Sulawesi and the moral values behind these traditions. This research is research qualitative with an ethnographic model. The source of the data is through the literature review source. Kasambu, as is known, is one of the many traditions that exist in Indonesia The Muna ethnic group certainly has a very important role in social life. This tradition still exists today adhered to, complied with and implemented by some Muna society, even in contemporary times has started to experience a shift, like use of sando services during childbirth replaced by medical personnel (midwife or doctor).